State Fund Placement Policy as an Instrument of Economic Stimulation: An Analysis of the Minister of Finance Decree No. 276 of 2025: Kebijakan Penempatan Dana Negara sebagai Instrumen Stimulasi Ekonomi: Analisis Keputusan Menteri Keuangan Nomor 276 Tahun 2025 - Inarotudduja (Yayasan Cerdas Pedia Indonesia, 2025)
This study examines the effectiveness of the Indonesian Government’s State Fund Placement Policy under Minister of Finance Decree No. 276/2025 as a counter-cyclical fiscal stimulus to accelerate bank credit to the real sector. Amid abundant banking liquidity and slowing credit growth, the policy injected IDR 200 trillion of government idle funds into state-owned banks to lower funding costs and boost lending. Drawing on secondary data from OJK, Bank Indonesia, the Ministry of Finance, and international institutions, a descriptive-analytic policy analysis assesses the design, governance, and transmission via the bank lending channel. Historical evidence from the 2020 Economic Recovery Program (PEN) and macro-financial indicators reveal demand-side constraints and regulatory gaps that may limit impact. The study finds that without clear technical regulations, robust oversight, and simultaneous improvements in investment sentiment, the policy risks suboptimal credit expansion. Strengthening governance frameworks and targeting priority sectors are critical to realize the multiplier effect and ensure efficient allocation.